Antibiotic Sensitivity and Resistance Patterns of Salmonella Typhi in Rajshahi Medical College Hospital (TAJ: Journal of Teachers Association, 2020)
Typhoid and paratyphoid fevers, collectively known as enteric fever, is caused by Salmonella enterica subspecies serovars Typhi and Paratyphi A, B and C. Despite this declining global trend, enteric fever is still considered to be a major public health hazard in Bangladesh and other developing countries due to poor sanitation, inadequate food safety measures and poor personal hygiene. In Bangladesh, the incidence of typhoid fever was reported to be 200 episodes per 100,000 person-years during 2003–2004. Multidrug-resistant (resistance to the first-line antimicrobials ampicillin, cotrimoxazole, and chloramphenicol) strains of S. Typhi and S. Paratyphi are on the rise globally and even cases of extensively drug-resistant (XDR) typhoid cases resistant to chloramphenicol, ampicillin, trimethoprim-sulfamethoxazole, third generation cephalosporins and fluoroquinolones are being reported from many corners of the world. This descriptive, observational study was carried out in Rajshahi Medical College Hospital Hospital, Rajshahi, Bangladesh from July 2017 to June 2019. Antibiotic sensitivity pattern of total 76 cases of enteric fever due to Salmonella Typhi were studied. Blood culture was carried out by BACT ALERT-3D, Automated blood culture analyzer from BioMeriuex SA, France Patented FAN Plus method. Based on the minimum inhibitory concentration (MIC), the organism was categorized as sensitive, intermediate, and resistant against the respective antibiotics as per Clinical and Laboratory Standards Institute (CLSI) criteria. We are reporting antibiotic sensitivity and resistant patterns of S. Typhi documented in Rajshahi Medical College Hospital, a large tertiary care hospital in Northern Bangladesh.TAJ 2020; 33(2): 10-14